Strategi Kampanye dan Branding Politik Anies Baswedan Melalui Instagram @Ubahbareng dalam Meraih Suara Generasi Z - Danang Febrianto; Martini; Dian Alfia Purwandari (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to find out what Anies Baswedan political campaign and branding strategy is through Instagram @ubahbareng in an effort to win the votes of generation z in the 2024, in this case the research focuses on the Instagram account @ubahbareng. The research period starts from November 2023 – Januari 2024 and takes place within the scope of ubah bareng. The method used in this research is descriptive qualitative with the aim of research being able to conduct more in-depth interviews with the ubah bareng team and students as representatives of generation z respondents. Apart from that, data collection techniques are carried out through observation, interviews, documentation, while data analysis techniques use data reduction, data presentation, drawing conclusions. The results of this research show that the campaign strategy carried out by Anies Baswedan and ubah bareng team is to create a space or forum that provides opportunities for the public to ask question directly, while in political branding it prioritizes the personality values of Anies Baswedan who prioritizes ideas and idea based politics. Generation Z offers new things in the way of political campaigning and providing space for aspirations, this is what ultimately becomes a concern for the younger generation to influence the decision to vote.